Library 2.0: Revolution or new makeup on an old way of working? - Lozano, Roser (Anuario ThinkEPI, 2009)
A reflection is made about the "Library 2.0" concept as a new way of understanding libraries, underlining that the use of the technology does not by itself define a Library 2.0, but rather the attitude toward users and, most importantly, good planning of both virtual and physical services. The innovations of recent decades are reviewed; in every case, it was thought that we were facing a revolution of the library model. Finally, we discuss whether the new concept of "Library 2.0" is really a revolution or will simply be absorbed inside the "old" model that we currently have.